Blue and fin whale residence time and occupancy in Navy training and testing areas off the U.S. West Coast - Lagerquist, Barbara A.; Irvine, Ladd M.; Follett, Thomas M.; Ampela, Kristen; Falcone, Erin A.; Schorr, Gregory S.; Mate, Bruce R.; Palacios, Daniel M. (Frontiers in Marine Science, 2024)
Blue (Balaenoptera musculus) and fin (B. physalus) whales are prominent species in the California Current Ecosystem (CCE) using the area for migration and foraging. Blue whales migrate between tropical wintering grounds and higher latitude foraging grounds in the CCE, whereas fin whales may remain there year-round. We used Argos tracks of 182 blue (mean duration: 78 days) and 98 fin (mean duration: 35 days) whales tagged from 1994-2018 along the U.S. West Coast to examine residence time and occupancy in U.S. Navy training and testing areas. Bayesian hierarchical switching state-space model locations calculated from Argos tracks were used to provide residence time and proportion of tracking duration within each Navy area. We also calculated relative occupancy isopleths from the state space models, for both directed and non-directed movement, to assess spatial use of Navy areas. We then used generalized linear mixed models and beta regression to examine relationships between Navy area use and covariates, including six climate indices. Point Mugu Sea Range (PMSR) was the most heavily used Navy area by both species in terms of whale numbers, followed by the Southern California Range Complex (SOCAL). Residence time was longest in PMSR for blue whales and in the Northwest Training and Testing Study Area (NWTT) for fin whales. Blue whale use in PMSR was greater in summer versus autumn and for whales tagged in Southern versus Central California. Proportion of tracking duration decreased in all areas with increasing values of the Oceanic Niño Index (ONI), and in PMSR, with increasing values of the North Pacific Gyre Oscillation. Fin whale residence time was longer in PMSR during summer than winter or spring and decreased with increasing values of Habitat Compression Index and ONI. Proportion of tracking duration for fin whales was greatest in summer in PMSR and in winter in SOCAL and NWTT. Overlap of directed and non-directed movement was greatest in PMSR for both species. This assessment of blue and fin whale residence time and occupancy in Navy areas improves our understanding of potential threats these animals face, not only from military activities in Navy areas, but throughout the CCE.